Clinic and ambulatory heart rates in patients with ischaemic heart disease and/or chronic heart failure taking rate-limiting medications: are they interchangeable?. Issue 1071 (25th November 2014) - Javed, Omar; Koo, Kenneth; El-Omar, Omar; Allen, Stuart; Squires, Alexander; El-Omar, Magdi
ABSTRACT: Background: The prognostic benefit from heart rate (HR) reduction in patients with ischaemic heart disease (IHD) and/or chronic heart failure (CHF) is now firmly established. Most decisions regarding initiation and/or dose adjustment of HR-limiting medications in such patients are based on clinic HR. Yet, this is a highly variable parameter that may not necessarily reflect HR control over the 24 h period. Objective: To examine the level of agreement between mean clinic and mean ambulatory HRs in patients with IHD and/or CHF taking rate-limiting medications. Methods: Prospective, observational study. Fifty patients with IHD and/or CHF who attended cardiology outpatient clinics at the Manchester Heart Centre and underwent same-day 24 h continuous ECG recording between March and October 2013 were included in the study. Mean clinic HR was compared with mean 24 h, daytime and night-time HRs. Limits-of-agreement plots were constructed to examine the relationship between the two HR measures in more detail. Results: The mean clinic HR was numerically similar to the mean HRs of all ambulatory time periods examined. However, on Bland–Altman plots, the limits of agreement between clinic and ambulatory HR means were quite wide, with the mean clinic HR ranging between 10.93 and 13.58 bpm below and 8.4 and 18.15 bpm above the mean ambulatory HR. Conclusions: Although numerically similar, the means of clinic and ambulatory HRs in patients with IHD and/or CHF display wide limits of agreement. As such, the two measures cannot be regarded as interchangeable.